PEMANFAATAN UANG SIMPAN PINJAM PADA BADAN USAHA MILIK DESA (BUMDES) DI DESA RAWA SEKIP KECAMATAN KUALA CENAKU KABUPATEN INDRAGIRI HULU - Danu Ibrahim; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is entitled “Utilization Of Saving Loan Money In Village Owned Enterprises (Bumdes) In Rawa Sekip Village, Kuala Cenaku District, Indragiri Hulu Regency”. The researcher was interested in raising this theme because of how the use of loan funds was used by the community for business capital or daily necessities. Data analysis conducted to answer the problems in this study is quantitative analysis that provides an overview of the actual condition of society, concerning the use of borrowed loans from BUMDes Rawa Mapan Savings and Loans units which are then analyzed based on the theories in this study. The following are the formulation of the problem: (1) How is the system of borrowing money at BUMDes Savings and Loans unit in Rawa Sekip Village, Kuala Cenaku District, Indragiri Hulu Regency, (2) What are the benefits of loan funds for beneficiaries of BUMDes Rawa Mapan Savings and Loans units in Rawa Sekip Village, Kuala Cenaku District, Indragiri Hulu Regency. Data collection techniques in this study are Questionnaire, Interview, and Documentation. The method of population collection and samples with Slovin techniques from 104 populations obtained 51 populations. From the findings in the field it can be seen that the loan fund program is not appropriate in the use of loan funds, which should be used as business capital but are used as daily necessities. This is due to the failure of the verification process to run optimally and the supervision of the business carried out and the existence of abuse and bad behavior by people who borrow loan funds. Keywords: Utilization, Savings and Loans, BUMDes Rawa Mapan